Lethal End of Spectrum of Clots-Thrombotic Storm - Muhammad Asim Rana; Ahmed F. Mady; Abdullah Ali Lashari; Rehab Eltreafi; Nicola Fischer-Orr; Kamal Naser (Case Reports in Critical Care)
Thrombotic storm (TS) is a rare, acute, hypercoagulable state characterized by multiple thromboembolic events affecting at least two different areas of the vascular system/organs over a short period of time. Typical triggers include inflammation, infections, minor trauma, surgery, pregnancy, and the puerperium. A single thrombotic event can set off a number of thromboembolic events, often including unusual locations like hepatic, portal, or renal veins, skin (purpura fulminans), adrenal glands, and cerebral sinus venous thrombosis. Usually, younger female patients are affected; in some patients, there is an association with an autoimmune disorder like lupus erythematosus, and they show evidence of antiphospholipid antibodies or other phenotypic expressions of anticoagulation disorders. The majority of patients have no previous history of thromboembolism. As the diagnosis of thrombotic storm relies solely on clinical symptoms with a lack of specific diagnostic tests, this can result in a delay of diagnosis. The treatment consists of uninterrupted lifelong anticoagulation. Sometimes immunomodulatory therapies have been used. The distinction between extensive thrombotic events like Heparin Induced Thrombosis (HIT), Thrombotic Thrombocytopenic Purpura (TTP), Antiphospholipids Syndrome (APS), and TS can sometimes be difficult, and the etiology of TS remains uncertain.